The Biorefinery of the Marine Microalga Crypthecodinium cohnii as a Strategy to Valorize Microalgal Oil Fractions - Moniz, Patricia (2022)
ABSTRACT: Chrypthecodinium cohnii lipids have been almost exclusively used as a source of Docosahexaenoic acid (DHA). Such an approach wastes the remaining microalgal lipid fraction. The present work presents a novel process to produce C. cohnii biomass, using low-cost industrial by-products (raw glycerol and corn steep liquor), in a 7L-bioreactor, under fed-batch regime. At the end of the fermentation, the biomass concentration reached 9.2 g/L and the lipid content and lipid average productivity attained 28.0% (w/w dry cell weight) and 13.6 mg/L h, respectively. Afterwards the microalgal biomass underwent a saponification reaction to produce fatty acid (FA) soaps, which were further converted into FA ethyl ester (FA EE). C. cohnii FA EE mixture was then fractionated, using the urea complexation method at different temperatures, in order to obtain a polyunsaturated fatty acid ethyl ester (PUFA EE) rich fraction, that could be used for food/pharmaceutical/cosmetic purposes, and a saturated fatty acid ethyl ester (SAT EE) rich fraction, which could be used as biodiesel. The temperature that promoted the best separation between PUFA and SAT EE, was -18 degrees C, resulting in a liquid fraction with 91.6% (w/w) DHA, and a solid phase with 88.2% of SAT and monounsaturated fatty acid ethyl ester (MONOUNSAT), which could be used for biodiesel purposes after a hydrogenation step.